The Implementation of Smart City Initiatives in Addressing Climate Change Challenges For The Transformation of Jakarta into a Resilient Global City - Dwiputra, Roby; Susetyo, Nurulitha Andini; Amanza, Apriano Hanindito (CSID Journal of Infrastructure Development, 2026)
Jakarta, a densely populated delta city and Indonesia's former capital undergoing post-relocation transformation, faces escalating climate change impacts, including land subsidence and tidal flooding. Annual subsidence rates of 5–25 cm in northern areas and recurrent tidal floods, including the December 2025 event, pose significant threats to urban sustainability and economic stability. This study employs a qualitative descriptive–analytic approach using a single-case study of Jakarta. Smart city initiatives are examined as governance instruments for climate resilience, drawing on secondary data from regulatory documents, real-time digital monitoring platforms, and global smart city performance indicators. The analysis applies thematic and comparative techniques supported by indicator-based assessment. The results show that smart city tools, notably the JAKI application and the Jakarta Satu geospatial portal, enhance real-time flood monitoring and early warning capabilities. These platforms improve inter-agency coordination during tidal flooding events by integrating water level data, spatial visualization, and citizen reporting. IoT-based sensor networks support faster operational responses and data-driven decision-making in flood-prone areas. Smart city implementation contributes positively to short-term adaptive capacity and emergency response effectiveness. During the December 2025 tidal flooding event, real-time dashboards across more than 170 IoT monitoring points enabled faster deployment of emergency resources in vulnerable northern districts. However, sensor coverage remains uneven in high-risk northern coastal zones. Digital access gaps limit participation among marginalized communities, reducing inclusivity. Governance challenges persist, including fragmented coordination and limited data transparency. Smart city initiatives remain largely reactive, with weak integration into preventive spatial planning and nature-based solutions. As a result, structural drivers of vulnerability, such as land subsidence and recurring coastal flooding, are not fully addressed. In conclusion, smart city initiatives represent a necessary but insufficient foundation for climate resilience in Jakarta; achieving the vision of a resilient and sustainable global city requires integrating digital systems with nature-based solutions, strengthening inclusive governance, and deepening cross-sector collaboration.